A Manifesto for Literary Studies - Garber, Marjorie B. (Book collections on Project MUSE., 2003)
This manifesto revives the ancient craft whose ultimate focus is language in action. In this book, Garber passionately concludes that "the future importance of literary studies - and, if we care about such things, its intellectual and cultural prestige both among the other disciplines and in the world - will come from taking risks, and not from playing it safe.""--Jacket